Angel in the sun : Turner's vision of history - Finley, Gerald E. (McGill-Queen's University Press, 1998)
J.M.W. Turner (1775-1851), widely known as perhaps the most eminent landscape painter of the romantic era, considered himself particularly a painter of historical landscapes. His distinctive landscapes were often enriched with symbolism and allegory that set them apart from those of his artist contemporaries and mystified his audiences. Angel in the Sun is an unconventional study of the richness and complexity of Turner's vision of history as revealed through his drawings and paintings.